2020
DOI: 10.1002/chem.201903279
|View full text |Cite
|
Sign up to set email alerts
|

Dialkylterphenyl Phosphine‐Based Palladium Precatalysts for Efficient Aryl Amination of N‐Nucleophiles

Abstract: Aseries of 2-aminobiphenyl palladacycles supported by dialkylterphenyl phosphines, PR 2 Ar' (R = Me, Et, iPr, Cyp (cyclopentyl), Ar' = Ar Dipp2 ,A r Xyl2f ,D ipp (2,6-C6H3-(2,6-C6H3-(CHMe2)2)2), Xyl = xylyl) have been prepareda nd structurally characterized. Neutral palladacycles were obtained with less bulky terphenyl phosphines (i.e.,M ea nd Et substituents) whereas the largest phosphines provided cationic palladacycles in whicht he phosphines adopted ab identate hemilabile k 1 -P,h 1 -C arene coordination m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Very recently, we have reported on the preparation of 2-aminobiphenyl palladacycles supported by a variety of dialkylterphenyl phosphane ligands developed in our research group, [13] and demonstrated their competence as precatalysts in a variety of C-N cross-coupling reactions. [14] This work extends these studies to N-substituted 2aminobiphenyl palladacycle analogues. Herein, we described the synthesis and the structural characterization of a series of N-methyl-and N-phenyl-substituted 2aminobiphenyl palladacycle bearing terphenyl phosphanes.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Very recently, we have reported on the preparation of 2-aminobiphenyl palladacycles supported by a variety of dialkylterphenyl phosphane ligands developed in our research group, [13] and demonstrated their competence as precatalysts in a variety of C-N cross-coupling reactions. [14] This work extends these studies to N-substituted 2aminobiphenyl palladacycle analogues. Herein, we described the synthesis and the structural characterization of a series of N-methyl-and N-phenyl-substituted 2aminobiphenyl palladacycle bearing terphenyl phosphanes.…”
Section: Introductionmentioning
confidence: 54%
“…40 ppm to higher frequency relative to the free phosphane. Comparison with NMR data found for other transition metals terphenyl phosphanes complexes, including palladium, [13,14,18] suggests monodentate coordination of phosphane in 1•L1 and 2•L1. Hence, it is safe to assume that the mesylate anion is coordinated to the metal center in these two palladacycles.…”
Section: Synthesis and Nmr Characterization Of Palladacyclesmentioning
confidence: 69%
“…Recently, we examined the behavior of a family of dialkylterphenyl phosphines in Pd-catalyzed aryl amination reactions using 2-aminobiphenyl-derived palladacycles as precatalysts. , We found that the cationic palladacycle with the sterically demanding phosphine PCyp 2 Ar Xyl2 , P1 (Scheme ), displayed excellent performance and provided a broader substrate scope in the amination of deactivated aryl chlorides with N -nucleophiles, including primary and secondary alkyl and arylamines and N -heterocycles such as indoles (Table ). To understand the reasons for the high activity and broad applicability of palladacycle P1 , we decided to investigate the mechanism of aryl amination reactions catalyzed by P1 , including the precatalyst activation step, by experiments and calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[9a-c,8e,9d] Sterically demanding phosphines are particularly interesting because they frequently exhibit air stability, intriguing metal arene interactions, and rare M•••H interactions, which are key to many metal-mediated organic transformations. [10] In this context, we recently reported the synthesis of sterically demanding mono-and bisphosphine ligands. The monophosphine ligands afforded rare [RuCl 2 (k-Pη 6 -arene)] type tethered Ru-arene complexes.…”
Section: Introductionmentioning
confidence: 99%